Tapestry bead crochet : projects & techniques - Benson, Ann (Sterling Pub., 2010)
Ann Benson brings a fresh look to classic romance, and crafters of all levels will fall in love with these 18 beautiful and stylish purses, carrying cases, and even a hat. Benson offers instructions on basic stitches and techniques. The bonus DVD shows many of the methods in action.